TRANSPARANSI KEUANGAN DAN KINERJA PADA WEBSITE PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA - Martani, Dwi; Fitriasari, Debby; Annisa, Annisa (Prosiding PESAT, 2013)
E-government in Indonesia is starting since the issuance of Presidential Instruction No.3/2003. The objective of this research to analysis the development of e-government whichfocuses on the financial and performance information transparency. Using a descriptiveanalysis on the 429 Indonesian local government websites during mid-May to July 2013,this research finds that the level of financial and performance information transparencyis 15%. Most local government website disclose financial and performance informationin the form of news and Local Government in Figures. While for the most importantfinancial and performance information in the form of budgets, financial statements andperformance reports are disclosed only by not more than 10% local government. Fromeleven local government with the best score, seven are located in Java and in the form ofcity.